Studying of 2,2′-Bipyrimidine Based Dyes Properties as Photo-Sensitizer for Dye Sensitized Solar Cells (DSSCs) - Krishnaveni, S.; Josephine, X. Mary; Sathyanarayanamoorthi, V. (Asian Journal of Chemistry, 2023)
In this investigation, five novel π-new organic donor-π-acceptor dyes (D-π-A) based on 2,2′-bipyrimidines were used. For optimization and DFT research, respectively, the 6-311+G(d,p) basis set and B3LYP density functional theory were applied. In all the systems, diphenyl amine moiety acts as the electron-donor component, whereas the nitro/cyano moiety as electron acceptor (anchoring) group. In the conjugated spacer, a methyl/ethyl substituent was used to examine the impact of the auxiliary donor group. The computed HOMO-LUMO gap and the spectral data matched well. The oscillator strength (f), electron injection free energy (ΔGinject) and light-harvesting efficiency (LHE) were also computed and explained. The calculated values for the examined dye-sensitizers open-circuit photo voltage (Voc) and electron coupling constant (VRP) were also included in this research. This study demonstrates that every synthetic dye has promising potential as a dye sensitized solar cells (DSSCs) sensitizer.